Komunikasi Kelompok Kaizer Team Dalam Game Online Pubg Mobile - Anggun Putri Dewanggi I.B; Muhammad Al Fitroh; Shinta Kristanty; Ahmad Pramegia (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
The reserach aims to understand to communication patterns formed within the Kaizer Tim group while playing the online game PUBG Mobile.Communication is a crutial element for archieving shared hoals, such as strategy, coordination, and teamwork. This study employs a qualitative approach with a descriptive method and uses a post-positivism paradigm. The study applies group conversation theory. Data were collected through non-participant observation, structured interviews, documentation, and litelature study. The study employs triangulation of data collection techniques. The results indicate that communication patterns whitin the team are influenced by certain factor, such as flekxible roles, emotional factors, and the use of communication technologies like the voice chat feature in the game. Communication within the Kaizer Team is informal with spesific circumstances, utilizing specitif codes to convey information, structured communication, and situational outcomes. The team’s structure and role are flexible. The study also highlights that adaptability to specific situations and the use of informal language are distinctive characteristics of the team’s communication. Inconclusion, clear communication patterns can contribute to the whole team members communication. In conclusion, clear communication patterns can contribute to the team’s success in the game. This study provides insights into the importance of communication within groups in online games